1996
DOI: 10.1071/ea9960203
|View full text |Cite
|
Sign up to set email alerts
|

Long-season wheats extend sowing opportunities in the central wheat belt of Western Australia

Abstract: Wheat cultivars and crossbreds with different maturities were tested at a range of sowing times from 1989 to 1991 at 13 sites in the central wheat belt of Western Australia. The aim was to determine if long-season cultivars would allow sowing before mid May, the earliest period estimated by previous studies. Rainfall in the growing season ranged from 176 to 330 mm. Long season cultivars showed the potential to extend the sowing season from early May into late April without loss of yield. Mid-season cultivars r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…This is 5 days longer than our observed (97 days) in Swift Current (1981–1990). Based on a three year cultivar×environment test in a rainfed area, Anderson et al [40] reported that early seeded long-season cultivars tend to outyielded mid-season cultivars with earlier or late seeding treatment. In a short season environment, Kerr et al [41] also found that cultivars with longer growth period can achieve higher yield if seeded early.…”
Section: Resultsmentioning
confidence: 99%
“…This is 5 days longer than our observed (97 days) in Swift Current (1981–1990). Based on a three year cultivar×environment test in a rainfed area, Anderson et al [40] reported that early seeded long-season cultivars tend to outyielded mid-season cultivars with earlier or late seeding treatment. In a short season environment, Kerr et al [41] also found that cultivars with longer growth period can achieve higher yield if seeded early.…”
Section: Resultsmentioning
confidence: 99%
“…This optimum is necessarily an average, for depending on the pattern of rainfall during the growing season earlier flowering crops may do better in one season, and later flowering ones may do better in another. As an average there is little room for further genetic improvement, though breeders have been producing slower maturing cultivars that can be sown earlier in the season while still flowering at the optimal time (Anderson et al 1996). Such cultivars allow farmers to capitalise on the flexibility in sowing time that their modern machinery and agronomic techniques enable, as mentioned earlier; they may also have environmental benefits in that their deeper roots may capture more water and nutrients that might otherwise escape towards the groundwater.…”
Section: Converting Biomass Into Grainmentioning
confidence: 99%
“…Such techniques greatly improve the timeliness of sowing and can thereby improve yields in water-limited environments where unreliable weather at the start of the growing season means that opportunities for sowing are best taken when they arise (Hobbs and Gupta 2003). Agronomic flexibility such as this requires a range of cultivars that are specifically suitable for early, mid, or late starts to the season (Anderson et al 1996).…”
Section: Capturing More Of the Water Supply: Reducing Losses From Soimentioning
confidence: 99%
“…Tactical management practices based on field experimentation and observation and applied immediately before and during the growing season may involve adjustments to seeding rates (Leach et al 1999;Tokatlidis 2014); variations in fertiliser rates (Jarvis and Bolland 1990;Robertson et al 2012), placement (Nyborg and Hennig 1969) and timing (Anderson 1985;Seymour et al 2016;Simpson et al 2016); changes to sowing time and choice of maturity class of cultivars (Anderson et al 1996;Stephens and Lyons 1998;Sharma et al 2008) and to seeding depth and method (Schmidt and Belford 1993); dry sowing (Kearns and Umbers 2010); use of herbicide, disease and pest tolerant or resistant cultivars (Jayasena et al 2018); and various chemical and nonchemical methods of weed management (Farooq et al 2011;Walsh 2016;. Tactical management practices and their timing are not a fixed sequence but will vary according to seasonal and market conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Although the choice of crop cultivar cannot be changed after sowing, we view the choice of cultivar as a component of tactical management because the decision may change depending on the timing of the opening rains and the likely length of the growing season (Anderson et al 1996). The use of cultivar mixtures (Fletcher et al 2019) could be seen as an aspect of tactical management in reducing the risks of such factors as terminal drought and frost damage, anticipated disease risk (Loughman et al 2000) or weed burden and resistance status.…”
Section: Introductionmentioning
confidence: 99%